Diarrhoeal disease related to agricultural wastewater and excreta use in Vietnam - Phuc Pham Duc; Hung Nguyen-Viet; Hattendorf, J.; Zinsstag, Jakob; Zurbrugg, C.; Phung Dac Cam; Odermatt, P. (2012)
The incidence of diarrhoea was monitored and the risk factors for diarrhoea were identified in the rural community of Hanam, Vietnam, over a period of one year. Compared to adults without direct contact to wastewater and excreta during their agricultural activities, those in direct contact had a higher incidence of diarrhoea.